1995
DOI: 10.1002/jsfa.2740670213
|View full text |Cite
|
Sign up to set email alerts
|

Changes in volatile compounds during maturation of some grape varieties

Abstract: The evolution of volatile compounds in three Vitis uinifera varieties (Monastrell, Cabernet Sauvignon and Tempranillo) was followed during maturation to determine whether they could be used as a maturation index. The volatile compounds were extracted and analysed by gas chromatography and gas chromatography-mass spectrometry. The volatile compounds of these nonaromatic varieties generally occurred in very low concentrations and only the C, compounds appeared in sufficiently high concentrations for their evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 7 publications
6
65
0
2
Order By: Relevance
“…FADP accounted for 99% of the volatile fraction of Frontenac gris, Frontenac blanc and Seyval blanc, whereas the proportion of FADP accounted for 96% and 90% of total quantified volatile compounds in the musts of St. Pepin and Vidal, respectively. In V. vinifera, C 6 compounds constitute the largest proportion of free volatile compounds in the socalled "neutral" varieties and are significant contributors to the herbaceous character found in grape musts [21]. In agreement with the present work, previous studies have shown that C 6 compounds are the main constituents of the flavor profile in several IHV varieties representing, in most cases, over 94% of total volatile compounds [3,22].…”
Section: Compounds and Other Fadpsupporting
confidence: 92%
“…FADP accounted for 99% of the volatile fraction of Frontenac gris, Frontenac blanc and Seyval blanc, whereas the proportion of FADP accounted for 96% and 90% of total quantified volatile compounds in the musts of St. Pepin and Vidal, respectively. In V. vinifera, C 6 compounds constitute the largest proportion of free volatile compounds in the socalled "neutral" varieties and are significant contributors to the herbaceous character found in grape musts [21]. In agreement with the present work, previous studies have shown that C 6 compounds are the main constituents of the flavor profile in several IHV varieties representing, in most cases, over 94% of total volatile compounds [3,22].…”
Section: Compounds and Other Fadpsupporting
confidence: 92%
“…In the red wines, 1-hexanol showed high values in Cabernet Sauvignon (1370.49 µg/L) and Tempranillo (1231.71 µg/L) wines; however, 1-hexanol was only present in trace amounts in the Cabernet Sauvignon from the Loess Plateau region of China (Jiang & Zhang, 2010). C6 compounds are partly responsible for the green and herbaceous aroma of grapes and wines (Gómez et al, 1995). High water status, especially during the later stages of ripening, could have negative effects on wine aroma.…”
Section: Alcoholsmentioning
confidence: 99%
“…In a previous study, the volatiles formed during the development of three types of non-aromatic grape cultivars revealed that only C6 volatile compounds were present in high concentrations; therefore, changes in the proportion of C6 volatile compounds can be used to confirm optimum maturity of the fruit (Gomez et al, 1995). Other studies revealed that the proportion of volatiles increased significantly after grape colouring (Park et al, 1991;Coelho, et al, 2007).…”
Section: Introductionmentioning
confidence: 97%